Research progress on the relationship between ACE2 ⁃ Ang ⁃ (1 ⁃ 7) ⁃ MasR axis and central nervous system diseases - LIANG He; LIN Jian⁃wen; MO Ming; XIE Lu⁃shuang; DU Shi⁃wei; LIU Yi (Chinese Journal of Contemporary Neurology and Neurosurgery, 2022)
Renin⁃angiotensin system (RAS) plays an important role in maintaining cardiovascular homeostasis, water and electrolyte balance in the body, and angiotensin converting enzyme Ⅱ (ACE2) and its axis of action angiotensin⁃(1⁃7) [Ang⁃(1⁃7)] and Mas receptor (MasR) composed of Ang⁃(1⁃7) and MasR axis can play an important role in this process, it can widely participate in the pathophysiological process of central nervous system diseases. Based on the structure and function of RAS, this study plans to sort out the latest relevant research results on the role of ACE2⁃Ang⁃(1⁃7)⁃MasR axis in ischemic stroke, cognitive dysfunction, anxiety state and neurodegenerative disease, improve the understanding of researchers and clinicians, and provide ideas for the development of new targets for central nervous system disease drugs in the future.